The Relationship Between Classroom Management Approaches And Learner Achievement At Primary Schools - Matsepe, Ramotsabi Dorrington (Central Univeristy of Technology, 2022)
South African society holds the education system accountable for all aspects of learner achievement. At the Department of Education in the Free State, the performance of learners was previously measured based on the matric year-end results only. This has however been re-evaluated as primary schools also make a major contribution to the process of developing learner achievement as these schools are the feeders into secondary schools. In this study, the researcher explored the relationship between classroom management approaches and learner achievement at primary schools. The study was grounded in Pavlov’s classical conditioning theory and Skinner’s operant conditioning theory. It was shaped by the research question: Is there a relationship between classroom management approaches and learner achievement at primary schools? The study used a quantitative approach with a correlation design. It used a survey and simple random sample to select the 162 teachers who completed a questionnaire. The findings revealed that the success approach was the most applied classroom management approach whilst the assertive approach was the least applied in primary schools. The results indicated no relationship between classroom management approaches and learner achievement at primary schools. The three primary school phases did not significantly differ on the application of the assertive approach, business academic approach, behavioural modification approach, group managerial approach and success approach. However, it should be noted that a significant difference existed between the Intermediate Phase and Senior Phase teachers on the application of the group guidance approach. Intermediate Phase teachers applied the group guidance approach more than Senior Phase teachers. As far as the application of the acceptance approach goes, Foundation Phase and Senior Phase teachers differed significantly, with Foundation Phase teachers applying this approach more than the Senior Phase teachers. Likewise, Intermediate Phase and Senior Phase teachers also significantly differed in the application of this approach, with Intermediate Phase teachers applying the acceptance approach more than Senior Phase teachers. Furthermore, the five school quintiles did not significantly differ on the application of the assertive approach, business academic approach, behavioural modification approach, group guidance approach, acceptance approach, success approach in the classrooms. Nevertheless, teachers in Quintile 1 and Quintile 3 primary schools differed significantly in the application of the group managerial approach with teachers in Quintile 1 schools applying this approach more. Still, teachers in Quintile 2 and Quintile 3 primary schools differed significantly on the application of the group managerial approach with teachers in Quintile 2 schools who apply this approach more. To minimize learner misbehaviour and manage the classroom effectively, this study recommends that primary school teachers should adopt classroom management techniques such as giving learners immediate feedback, applying rewards in the classroom, knowing the socio-economic backgrounds of their learners and providing lockers in the classrooms.
Dissertation
Keywords: Acceptance approach; Assertive approach; Behavioural modification approach; Business academic approach; Classroom management approaches; Group guidance approach; Group managerial approach; Learner achievement; Primary schools; Success approach